Alzheimer's disease and cerebrovascular disease biomarkers in older adults with mild cognitive impairment or major depressive disorder. (December 2021) - Golas, Angela C.; Salwierz, Patrick; Rajji, Tarek K.; Bowie, Christopher R.; Butters, Meryl A.; Fischer, Corinne E.; Flint, Alastair; Herrmann, Nathan; Mah, Linda; Mulsant, Benoit H.; Pollock, Bruce G.; Taghdiri, Foad; et al.
Abstract: Background: Mild Cognitive Impairment (MCI) and Major Depressive Disorder (MDD) are independently associated with increased risk of dementia. Cerebrospinal fluid (CSF) and neuroimaging biomarkers can help to elucidate the etiology of cognitive impairment. We compared CSF biomarker profiles of Alzheimer's disease (AD) and white matter hyperintensities (WMH) across three groups: MCI, MDD, or comorbid MCI+MDD. Method: We measured CSF total tau, p‐tau, amyloid‐β42, using a sandwich ELISA method (Innotest, Fujirebio), and calculated p‐tau/amyloid‐β42 ratio in 31 participants diagnosed with MCI (N=13), MDD (N=7), or both MCI and MDD (N=11) enrolled in the Preventing Alzheimer's dementia with cognitive remediation plus transcranial direct current stimulation in mild cognitive impairment and depression (PACt‐MD) study. All diagnoses were made in accordance with NIA‐AA and DSM 5 criteria. Participants with p‐tau > 68 pg/mL and ATI < 0.8 were considered AD (+). WMH were quantified on T2‐weighted magnetic resonance images in 27 of the participants. We compared CSF AD biomarkers across diagnostic groups. We then compared cognitive performance and WMH in those with AD (+) versus AD (‐) CSF biomarkers. Result: 9/31 participants exhibited AD (+) CSF: 7/13 with MCI and 2/11 with MCI+MDD. Participants with AD (+) CSF showed more impairment in verbal memory, working memory, language, and overall cognition than those with AD (‐) CSF (p=0.02, p=0.04, p=0.04, and p=0.03, respectively). 26/27 (96%) participants exhibited moderate to severe WMH irrespective of diagnosis or AD biomarker status. Conclusion: Few participants in our sample with MDD had an AD (+) CSF biomarker profile, despite a neurocognitive profile of MCI. All participants with AD (‐) CSF had moderate to severe WMH, including those with MDD alone. Further investigation should determine whether volume or distribution of WMH contribute to cognitive impairment or depression in MCI patients who have an AD (‐) CSF biomarker profile.